The potential effects of nanoparticles in gene regulation and expression in mammalian, bacterial and plant cells – A comprehensive review - Ayesha Javaid; Neelma Munir; Zainul Abideen; Bernardo Duarte; Zamin Shaheed Siddiqui; Rukhama Haq; Shagufta Naz (Plant Nano Biology)
Gene regulation and expression are fundamental, though challenging life processes involved in the development and rectification of various cellular mechanisms. Nanoparticles have been employed as gene regulatory systems that can efficiently modulate gene expression owing to their unique physiochemical properties. Exposure to metal, metal oxide, carbon and polymer-based nanomaterials can lead to arbitrary DNA methylation and thus damage targeted cells by generating oxidative stress genes in mammals and bacteria. However, the valuable role of carbon-based nanoparticles in the suppression of tumor growth factor genes or genes attributed to inhibition of angiogenesis is an innovative approach in medical science, which may stop the progression of abnormal cells. Predominantly, nanoparticles induced the genes involved in oxidative stress, DNA methylation, pro-inflammatory reactions, signaling pathways, cell proliferation and differentiation. The expression of toxin-antitoxin genes in bacteria is also controlled by nanoparticles, such as ZnO, which inhibits biofilm formation in bacteria and is responsible for antibiotic resistance. Exposure of plants to several types of nanoparticles upregulated the genes involved in shielding the plants against oxidative and abiotic stresses, predominantly salinity stress. Gene modulation by nanoparticles in different organisms or species is not uniform. This article describes gene regulation and expression studies performed in nanoparticle-exposed mammalian, bacterial, and plant cells. This review will help researchers to upgrade gene regulation approaches, complementing the potential of nanomaterials in regulating cell activities, thereby embarking on their use in therapeutics for many genetic diseases.